2014
DOI: 10.1016/j.sbspro.2014.11.151
|View full text |Cite
|
Sign up to set email alerts
|

IT Adoption by Internal Auditors in Public Sector: A Conceptual Study

Abstract: This study is initiated by the interest in understanding Information Technology (IT) adoption by government internal auditors.With the tremendous development of IT in public sectors such as e-government that has been developed to support National IT and transformation agenda, the auditors also are expected to equip not only with the knowledge of IT but also with the tools required to work with this situation. The objectives of this study are to investigate the current IT adoption among internal auditors and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…The TOE framework provides a systematic classification of influencing factors and has been widely applied in existing technology adoption studies (Liu et al, 2011;Xu, 2012;Ahmi et al, 2014;Gangwar et al, 2015). In addition to the three dimensions of context, Songer et al (2001) suggested to introduce economic factors into the technology adoption framework, considering that firms may attempt to use the information technology if at a low cost.…”
Section: The Technology-organization-environment Framework (Toe)mentioning
confidence: 99%
“…The TOE framework provides a systematic classification of influencing factors and has been widely applied in existing technology adoption studies (Liu et al, 2011;Xu, 2012;Ahmi et al, 2014;Gangwar et al, 2015). In addition to the three dimensions of context, Songer et al (2001) suggested to introduce economic factors into the technology adoption framework, considering that firms may attempt to use the information technology if at a low cost.…”
Section: The Technology-organization-environment Framework (Toe)mentioning
confidence: 99%
“…In particular, most prior TAM research investigates the end-users’ acceptance of non-auditing-related technology such as word processing (Davis et al , 1989; Adams et al , 1992), personal computing (Igbaria et al , 1997), data retrieval systems (Venkatesh and Morris, 2000), and accounting systems (Venkatesh and Morris, 2000; Venkatesh et al , 2003). While some extant GAS acceptance research has been done, most of this research either focusses on the use of GAS for internal auditing (Kim et al , 2009; Ahmi et al , 2014), or on a mixture of internal and external auditing (Janvrin et al , 2008; Ahmi and Kent, 2013). Also, this prior research does not give a weight to the factor of technology features and their possible impact on the acceptance enablers, with exception to Kim et al (2009) that was also focussing on GAS acceptance by internal auditors.…”
Section: Introductionmentioning
confidence: 99%
“…Francis, (1994), cited in Nagy, Cenker, (2007) added that those changes lead to the works of accounting professions to be structured and standardized, but has limited their subjectivity. Lack of conceptual skills and professional judgment capabilities disqualify them to stay relevant not only in Malaysia but also across international borders.…”
Section: Research Problemsmentioning
confidence: 99%
“…Janvrin D., Bierstaker J., and Lowe J. D., (2009) asserted that whether it is auditors or the clients, the use of information system (IS) tools is a norm in the technology world. Ahmi, Saidin, Abdullah, (2014) however, implied that if they have not fully adopted IS, they should at least be in the process of adoption or having a positive perception towards technology usage. It is unknown exactly how powerful new technology will change our lives and works.…”
Section: Research Problemsmentioning
confidence: 99%
See 1 more Smart Citation